Accounting Information System: User Participation and Organizational Commitment - Sri Dewi Anggadini; Sari Damayanti; Natasha Puspa Dewi; Deden Abdul Wahab Sya'roni (AFRE (Accounting and Financial Review), 2021)
User participation and organizational commitment are important things that can improve the performance of accounting information systems. This study aims to determine the effect of user participation and organizational commitment on the performance of accounting information systems. This study uses a quantitative approach with descriptive and verification analysis methods. The research was conducted by distributing questionnaires to employees of the accounting and systems division at Medco Energi Company with 45 respondents. The results of this study indicate that user participation and organizational commitment have a positive effect on the performance of accounting information systems. This research provides important information that no matter how well an accounting information system is implemented, it will not succeed without the support of user participation and organizational commitment.DOI: https://doi.org/10.26905/afr.v4i2.6001